Trade Liberalization, Domestic Trade Policies and the Failure of Reducing Poverty: The Case of Indonesia - I Gusti Ngurah Parikesit Widiatedja (Sociological Jurisprudence Journal, 2021)
The existence of international trade has provided important benefits for reducing poverty. Many countries then have concluded trade agreements, to reach this goal by committing trade liberalization. The relatively high number of poverty has raised some concerns, questioning the effectiveness of trade liberalization. Putting Indonesia as a case study, this article weighs the role of trade liberalization and domestic trade policies in reducing poverty. This article argues that the existence of domestic trade policies is more significant than trade liberalization. The unfair practices, corruption, and the overwhelming spirit of national interest that colour domestic trade policies, contribute to the failure of reducing poverty instead of trade liberalization.